INTEGRASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM - Siti Indria Puspita Sari; Fitri Siti Sundari; Dendy Saeful Zen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The Integration of a character education in science subject on student of the fifth grade of Margajaya 3 Elementary School, Bogor Barat 2022/2023. Final project of the department of teacher elementary school in Pakuan University., Bogor, 2022. Kinds of this research with the qualitative research onstudy case. The subject of this research is one of the student fifth class on student of Margajaya 3 elementary school Kota Bogor. The technique of the collect this research with the observation, interview and documentation. The data is analizingby reduction unrelevant data, display the data systematically, and the result is focus on the research. The result of the research showed that student has been intergrated with the caracter education which implemented in science subject. Which means that in determining the appropriate character the subject matter and integrate these characters into the learning material of natural sciences. By making character education successful in schools related to adequate learning facilities and resources, so that the curriculum that has been designed can be implemented optimally. The purpose of this research are to create and train the ability of student continuously to a better way. Learning of the sience subject the education of caracterhas been given to build the caracter of religious, honest, discipline, caracter hard work, independent, sosial care, responsibility, tolerance, curiosity and value opinion.